An observational study from a new tertiary care hospital in North Odisha: clinical and etiological profile of acute ischemic stroke patients - Behera, Bibhu P.; Mohanty, Partha S. (International Journal of Advances in Medicine, 2019)
Background: Worldwide, cerebrovascular accidents (stroke) are the second leading cause of death and the third leading cause of disability. According to WHO estimation, by 2050 nearly 80% of stroke cases may occur in low and middle-income countries like China and India. It is critical that we understand the etiology causing the stroke so that appropriate treatment can be initiated in a timely fashion. Furthermore, understanding the risk factors associated with stroke is important before primary and secondary preventive measures can be prescribed to the patient. Methods: This observational study was carried out amongst 481 acute ischemic stroke patients that fulfils the inclusion and exclusion criteria and admitted in medicine ward of Pandit Raghunath Murmu Medical College and Hospital, Baripada, Dist. Mayurbhanj, Odisha, India from June 2018 to January 2019. Results: In our study, 481(60.43%) patients had ischemic stroke and 315 (39.57%) patients had hemorrhagic stroke. The incidence of stroke is maximum in 51-70 years of age group which comprises of 59.46% of total patients. The average age + SD were 61.4±13.1 in our study. The most common risk factor was hypertension with 69.85% followed by dyslipidemia 51.77%. Most common clinical presentation was hemiplegia (72.35%) followed by speech involvement (59.46%). Most common site of infarct was parietal (22.25%), followed by periventricular (12.68%). Conclusions: Most of the patients had ischemic stroke as compared to hemorrhagic stroke. It was more common in males. The study contributes to understanding of demographic characteristics, risk factors, and stroke subtypes in acute ischemic stroke. The importance of various risk factors among ischemic stroke subtypes should be stressed for prompt preventive strategies and treatment.